Understanding the Adoption of Autonomous Vehicles in China Based on TRI and TAM - Xiuhong He; Heng Zhang; Ju Guo; Yingchun Wang (World Electric Vehicle Journal)
Autonomous vehicles (AVs) represent a notable advancement in automotive technology, with the potential to enhance road safety, decrease energy consumption, and mitigate environmental pollution. This study aims to advance the understanding of AV development by proposing a research framework centered on the framework of “personality–perception–behavioral intention”. This framework is utilized to examine the influence of consumers’ personality traits and perceptions on their intention to adopt AVs. The research model was empirically tested using data collected from 310 questionnaires. The findings indicate that consumers’ personality traits, specifically optimism and innovativeness, along with their perception of the usefulness of AVs, exert a significant positive influence on their adoption intentions. Furthermore, the impact of these factors varies considerably across different consumer segments. Conversely, factors such as discomfort, insecurity, and perceived ease of use do not demonstrate a significant effect on the intention to adopt AVs.